2016
DOI: 10.1038/ng.3508
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 polymorphisms alter thiopurine metabolism and hematopoietic toxicity

Abstract: Widely used as anti-cancer and immunosuppressive agents, thiopurines have narrow therapeutic indices due to frequent toxicities, partly explained by TPMT genetic polymorphisms. Recent studies identified germline NUDT15 variation as another critical determinant of thiopurine intolerance, but the underlying molecular mechanisms and its clinical implications remain unknown. In 270 children enrolled in clinical trials for acute lymphoblastic leukemia in Guatemala, Singapore, and Japan, we identified 4 NUDT15 codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
639
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(679 citation statements)
references
References 61 publications
29
639
5
6
Order By: Relevance
“…Multiple strong transcription factors and H3K27Ac binding signal can be detected around this rs554405994-located region according to the epigenomic information from public resource (i.e., Epigenome Browser [38], Figure 6C), indicating variant allele of rs554405994 may be associated with NUDT15 expression through altering the binding affinity of transcription factors with gene promoter. Interestingly, rs554405994 also induces a GlyVal insertion between position 18 and 19 of NUDT15, and causes a slight reduction in NUDT15 activity according to the previous report [24]. Therefore, rs554405994 can impact thiopurine metabolism through both down-regulating gene expression and reducing enzyme activity, thus may be considered as a new causal variant for thiopurines-induced myelotoxicity.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Multiple strong transcription factors and H3K27Ac binding signal can be detected around this rs554405994-located region according to the epigenomic information from public resource (i.e., Epigenome Browser [38], Figure 6C), indicating variant allele of rs554405994 may be associated with NUDT15 expression through altering the binding affinity of transcription factors with gene promoter. Interestingly, rs554405994 also induces a GlyVal insertion between position 18 and 19 of NUDT15, and causes a slight reduction in NUDT15 activity according to the previous report [24]. Therefore, rs554405994 can impact thiopurine metabolism through both down-regulating gene expression and reducing enzyme activity, thus may be considered as a new causal variant for thiopurines-induced myelotoxicity.…”
Section: Resultsmentioning
confidence: 64%
“…As down-regulation of NUDT15 in cell lines can also sensitize leukemia cells to thiopurines [24], we thus conducted an eQTLs analyses for NUDT15 to search additional potential pharmacogenetic markers in this gene. Expression level and SNP genotypes of LCLs were retrieved from the public resource (see Methods), and submitted for association analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among East Asian and Hispanic populations, four coding variants (p.Arg139Cys, p.Arg139His, p.Val18Ile, and p.Val18_Val19insGlyVal) result in over 75% loss of nucleotide diphosphatase activity. In a recent study, this information was used to classify patients as normal, intermediate, or low NUDT15 activity and their dose of 6-MP was prospectively modified during maintenance [73]. Guidelines from the Clinical Pharmacogenetics Implementation Consortium (CPIC) are currently being updated to include dosing recommendations for patients with NUDT15 variants [74].…”
Section: Hematologic Toxicitymentioning
confidence: 99%
“…For instance, investigators in an international collaboration identified genetic polymorphisms associated with thiopurine toxicity has a major implication for care of subgroups of children in all settings. 175 The explosion of data arising from tumour genome sequencing comes almost exclusively from high-income countries; sequencing of samples from LMICs might yield important implications for therapy for children in both LMICs and high-income countries. Innovative programmes such as medical telecommunication could improve access to quality cancer care for children in LMICs and have application to underserved populations in high-income countries.…”
Section: Paediatric Oncologymentioning
confidence: 99%